2013
DOI: 10.4321/s1139-76322013000400016
|View full text |Cite
|
Sign up to set email alerts
|

Prevención del embarazo en la adolescencia

Abstract: Adolescent pregnancy prevention El embarazo en la adolescencia continúa siendo un problema de salud pública en España, tanto por sus consecuencias como por sus tasas mantenidas. En marzo de 2013, el grupo PrevInfad realizó una actualización de sus recomendaciones sobre esta cuestión y en este artículo se presenta la introducción general al tema, en cuanto a su magnitud, y se exponen los resultados de la revisión de la evidencia sobre la efectividad del consejo desde la Atención Primaria pediátrica y las recome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…Rejection of pregnancy, fear of the parents' reaction and lack of knowledge about pregnancy have been proposed as variables that impede obstetric control in adolescent pregnant women [24]. It known that if prenatal care is adequate, the pregnancy outcome in adolescents over 15 years old are comparable to pregnancies in adult women [42], and reduce obstetrical complications [2]. Therefore, it is important to promote obstetrical control from the earliest stages of pregnancy, since it has been shown that the social context, associated with inadequate prenatal follow-up, raise the risk of maternal-fetal complications even more than the biological immaturity of the woman [2,4,37,43].…”
Section: Discussionmentioning
confidence: 99%
“…Rejection of pregnancy, fear of the parents' reaction and lack of knowledge about pregnancy have been proposed as variables that impede obstetric control in adolescent pregnant women [24]. It known that if prenatal care is adequate, the pregnancy outcome in adolescents over 15 years old are comparable to pregnancies in adult women [42], and reduce obstetrical complications [2]. Therefore, it is important to promote obstetrical control from the earliest stages of pregnancy, since it has been shown that the social context, associated with inadequate prenatal follow-up, raise the risk of maternal-fetal complications even more than the biological immaturity of the woman [2,4,37,43].…”
Section: Discussionmentioning
confidence: 99%
“…Los problemas de salud sexual mencionados anteriormente se manifiestan principalmente en individuos con edades comprendidas entre los 15 y los 25 años. Se podría afirmar que este grupo de edad presenta el riesgo más elevado y una mayor vulnerabilidad (Colmer, 2013). De ahí surge el interés de enfocar esta investigación en la población adulta joven.…”
Section: Introductionunclassified